Monitoring Chronic Non‐Cancer Pain in Denmark Over Two Decades: Prevalence, Mental Health and Loneliness - Ekholm, Ola; Herling, Suzanne Forsyth; Lykke, Camilla; Skurtveit, Svetlana; Hamina, Aleksi; Sjøgren, Per; Kurita, Geana Paula (European Journal of Pain, 2025)
ABSTRACT Background Epidemiological surveys have monitored chronic non‐cancer pain (CNCP) and investigated associated factors in Denmark for more than 20 years. This study aimed to analyse CNCP prevalence in the Danish population from 2000 to 2023 and its associations with mental health status and loneliness. Methods Population‐based surveys were conducted between 2000 and 2023. In all waves, residents aged ≥ 16 years were randomly selected to complete a self‐administered questionnaire. Samples included 10,089 respondents in 2000, 5292 in 2005, 14,330 in 2010, 13,429 in 2013, 13,050 in 2017, 10,384 in 2021 and 9303 in 2023. CNCP was defined as pain lasting ≥ 6 months. Mental status was assessed by Mental Component Summary score of Short Form‐12 and severe loneliness by the Three‐Item Loneliness Scale. Calibration weighting was applied to reduce potential non‐response bias. Results The prevalence of CNCP increased steadily by 9.4 percentage points from 2000 (19.5%) to 2023 (28.9%), but with a downward tick during the COVID‐19 pandemic in 2021 (25.3%). Women aged 45 years or older had the highest prevalence in all waves. Results showed a worsening of mental health over time in both individuals with and without CNCP; however, the lowest scores were reported by individuals with CNCP. Severe loneliness seemed to be a substantial problem in individuals with CNCP (17.3% in 2021). Conclusions In summary, CNCP was highly prevalent over the given period and associated with mental health status and severe loneliness in recent years. Significance This study demonstrated alarming trend on chronic non‐cancer pain prevalence over time in Denmark. The high estimates of prevalence and related issues, such as mental health and severe loneliness deserve further investigation and prioritisation in the public health agenda.